Penerjemahan Istilah Robotika dari Bahasa Inggris ke Bahasa Indonesia - Nurmalia, Lia; Nisa, Baiatun; Arifin, Soraya Farantica; Purwaningrum, Prapti Wigati (Kementerian Sekretariat Negara Republik Indonesia, 2022)
The objective of this research is to examine the use of translation strategies to translate robotics terms in Big Hero 6 – Hiro to the Rescue novel from English to Indonesian. The aim is to find out what strategies the translator mostly uses to translate robotics terms. This research uses qualitative method where the result of research with this method is strongly influenced by the views, thoughts, and knowledge possessed by the researcher. Through the research, from seventeen translation strategies, the translator uses seven translation strategies to translate robotics terms in the novel. Those translation strategies are: (1) transposition 15 times or (46%), (2) naturalization 5 times or (15%), (3) literal 4 times or (12%), (4) modulation 4 times (12%), (5) reduction 1 times (3%), (6) descriptive equivalent 2 times or (6%), and (7) transfer 2 time (6%). Therefore, more that 50% robotics terms are translated by using transposition strategy. It is inferred that there are some changing position of words and phrases from English to Indonesian so that the translator must find the most equivalent translation by finding the nearest style in TT. Keywords: novel, robotics terms, translation strategy